Método e linguagem para modelagem gráfica de requisitos de software e sistemas - Novaes, Paulo José Dantas (2019)
This dissertation proposes a method and a language for graphic modeling of software and systems requirements, under the name of RIMON (Requirements and Interdependencies MOdeling Notation). This language allows to represent requirements and their interdependencies in a systematic, precise and expressive way, aiming to contribute to the quality improvement of software and systems requirements specifications. Sourced in concepts of RON (Requirements Oriented to Notifications) approach, RIMON was designed to be visually attractive in its possible commercial usage. This attractiveness results from a development grounded in the Physics of Notations (PoN), which provides principles for creating efficient visual notations in terms of communication. In addition, the language is defined by an abstract syntax (metamodel) and a concrete syntax (visual syntax), complemented by a precise semantic mapping. Regarding the proposed method, it includes a set of steps for identification and analysis of input data, graphical requirements and interdependencies modeling. RIMON offers features such as support for modeling functional and nonfunctional requirements, entities, attributes, preconditions, postconditions and conflict identification. As a notable characteristic, the modeling of preconditions allows the representation of constraints related to non-functional requirements by means of attributes containing logical-mathematical conditions. At last, this work presents three modeling experiments using RIMON, including system requirements (extracted from the literature) and software requirements (real project) environments, designed to demonstrate and verify the capabilities of the language.